The role of psychological counseling in comprehensive work with clients suffering from alopecia - Breurosh, Bohdan (Global Prosperity, 2024)
Abstract. When doctors look at alopecia, they see a dermatological condition. Hair follicles stop working, prescribe treatment, come back in three months. But people living through this tell a completely different story. A woman wakes up finding clumps of hair on her pillow. A young man watches his temples going bald rapidly. A teenager loses half their hair in a week. What follows isn't just about scalp and follicles - it's panic, anxiety turning chronic, depression, social withdrawal. Hair isn't just keratin strands. It's part of identity, how someone sees themselves, how society judges them. Unlike diabetes or heart problems you can hide, alopecia sits right there on your head for everyone to see. Every conversation, every meeting becomes stressful. Medical treatment focuses on hair regrowth - logical, seemingly. But even when hair grows back, the person inside is already broken. Research shows people with alopecia suffer anxiety disorders, depression, social phobia at much higher rates. Quality of life plummets. Yet psychological support remains practically absent from treatment protocols. This article examines why psychological counseling must be standard care for alopecia, not optional extra. Using theoretical analysis, we explore psychological impacts, relevant frameworks, effective counseling approaches, and integrated care models. People losing hair deserve real help addressing both physical and psychological dimensions of their suffering.